Pengaruh Kredibilitas Celebrity Endorser, Desain Iklan, dan Relevansi Pesan terhadap Sikap dan Minat Beli Produk - Nur Hasna Hamidah; Diah Kusumawati (Jurnal Komunikasi Massa, 2025)
The increasing complexity of marketing communication dynamics underscores the importance of advertising effectiveness in shaping consumer attitudes and purchase decisions. This study aims to examine the contribution of endorser credibility, advertisement design appeal, and message relevance to consumers’ attitudes toward the product and purchase intention. The advertisement under investigation is “Teh Kotak Satu-satunya.” The theoretical framework is grounded in cognitive response theory, derived from the Stimulus–Organism–Response (S-O R) model, which positions attitude as a conceptual bridge between external stimuli and behavioral responses. Advertisement design is analyzed using Moriarty’s concept; celebrity endorser credibility is examined through Ohanian’s model; and message relevance is explained through relevance theory and the central route of the Elaboration Likelihood Model (ELM), which emphasizes the importance of deep message processing by the audience. Employing a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis of 96 respondents who follow the Teh Kotak Instagram account, the findings indicate that the proposed PLS-SEM model of attitude and purchase decision demonstrates an acceptable model fit (SRMR = 0.085; GoF = 0.37). Endorser credibility was found to have the strongest contribution (f-square = 0.082) to product attitude, followed by message relevance (f-square = 0.049). Furthermore, product attitude significantly influenced purchase intention and acted as a mediator in the relationships between endorser credibility (p-value = 0.029) and message relevance (p-value = 0.052) and purchase intention. In contrast, advertisement design appeal only influenced general attitude toward the advertisement (p-value = 0.000) and did not contribute to product attitude or purchase intention. The findings suggest that persuasive communication strategies on Instagram for low-involvement products should prioritize communicator credibility and message relevance in order to enhance product appeal and stimulate purchase intention.